Specification of fact calculations within the MetaMIS approach - Roland Holten; Alexander Dreiling (Westfälische Wilhelms-Universität Münster, Institut für Wirtschaftsinformatik, 2002)
Based on recent work on the so called MetaMIS approach we show how fact calculations can be specified from a management point of view. The MetaMIS approach's intention is to specify management views on business processes. It comprises a language, a representation formalism and guidelines to define information required for management decisions. Information in general should have pragmatic meaning for the management user. Beyond the task of specifying information in this sense, fact calculations are required to manipulate information. Respective analyzing tasks typically deal with variances, growth rates and other relevant aspects of business processes. We extend the MetaMIS approach to enable the specification of fact calculations in data mart environments.
Keywords: 650